Modelling of evolutions of potentials and deformations for aluminium alloy, chilling in three-dimensional space pattern - A. N. Chichko; E. A. Drozdov; O. I. Chichko (Литьë и металлургия)
The method of computer modeling, synthesizing cell- automatic approach and equations of termoelasticity for the processes, proceeding at crystallization of metal invironment, is offered. The three-dimensional computer calculations of the structure such as ’’cross", filled by aluminium alloy, having a nonuniform temperature field, received during filing of the mold by metal, are carried out.